2013
DOI: 10.1111/avj.12013
|View full text |Cite|
|
Sign up to set email alerts
|

Cat admissions toRSPCAshelters in Queensland,Australia: description of cats and risk factors for euthanasia after entry

Abstract: Objective A lack of information limits understanding of the excess cat problem and development of effective management strategies. This study describes cats entering Royal Society for the Prevention of Cruelty to Animals (RSPCA) Queensland shelters and identifies risk factors for euthanasia.Methods Data for cats entering relevant shelters (July 2006-June 2008 were obtained from the RSPCA's electronic database. Univariable and multivariable logistic regression analyses were conducted to identify risk factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
110
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(126 citation statements)
references
References 23 publications
14
110
1
1
Order By: Relevance
“…This supports the view that desexing of prepubescent female cats (<4 months old) could make a significant difference to cat welfare by reducing the numbers of kittens surrendered to shelters. [8] It could also reduce supplementation of feral cat populations with abandoned kittens. [11] There is support among cat rescue organisations for desexing prepubescent cats, with 19 of the 29 cat rescue organisations that replied to a survey on the topic agreeing that it would be beneficial in reducing the number of homeless cats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the view that desexing of prepubescent female cats (<4 months old) could make a significant difference to cat welfare by reducing the numbers of kittens surrendered to shelters. [8] It could also reduce supplementation of feral cat populations with abandoned kittens. [11] There is support among cat rescue organisations for desexing prepubescent cats, with 19 of the 29 cat rescue organisations that replied to a survey on the topic agreeing that it would be beneficial in reducing the number of homeless cats.…”
Section: Discussionmentioning
confidence: 99%
“…[7] These kittens may be the offspring of stray or feral cats, or of pet cats that are not desexed until after they have bred. [8] A Queensland study found that 83% of pet cats were desexed before they were 1 year old [9] (lower than the estimates of desexed status for all pet cats) and a national study found that 88% of all pet cats were desexed and 94% of those aged over 1 year. [10] …”
mentioning
confidence: 99%
“…In 2003, 76,321 (57%) cats were euthanized in Michigan shelters alone with the estimated ratio of euthanized cats to cats who had owners to be 3.1% (Bartlett et al 2005). Also in Australia, more than half of the stray and unwanted cats admitted to animal shelters are euthanized (Alberthsen et al 2013). In Japan, 93% out of 164,308 cats admitted to animal shelters were euthanized in 2010; the number remaining largely unchanged for a long time (Onodera et al 2014).…”
mentioning
confidence: 99%
“…An initial pilot study was undertaken to establish the validity of the data collected and develop the methodology for the larger study. This pilot was published (Alberthsen, Rand et al 2013),…”
Section: Overviewmentioning
confidence: 99%
“…Cats were retrospectively categorised as having been sterilised prior to admission or not, based on a modified version of the methodology described in Alberthsen, et al (2013) (see Chapter 4). Under the modified method, cats with 'yes' for sterilised and without a recorded sterilisation date were assumed to have been sterilised prior to admission.…”
Section: Definitionsmentioning
confidence: 99%